Difference in the association of food security and dietary diversity with and without imposed ten grams minimum consumption - Trias Mahmudiono; Dwi Putri Pangesti Suro Andadari; Calista Segalita (SAGE Publishing, 2020)
Background: Dietary diversity measurement is one of the simple tools to assess the quality of food consumed in population-level and endorse by many international agencies. However, there is a growing concern that the current dietary diversity measures were lacking in the sensitivity due to the omission of minimum food consumed to be considered as consuming certain food groups in the calculation of dietary diversity score. The purpose of this study is to find the difference in DDS measurement between two methods by applying a 10-grams minimum intake for all food groups and the other one, without. Design: A cross-sectional studies involving 55 samples from two villages with different geographical characteristics. Methods: One village represents the agricultural area; other was fishpond/coastal area. Dietary diversity was analyzed using Individual Dietary Diversity Score (IDDS) with 9 food categorizations. Dietary diversity measurement calculated based on the food recall with consideration of 10 grams minimum of food weight consumption. Mann Whitney Test used to analyze the difference between calculation of dietary diversity score with and without minimum 10-grams. Results: There is no difference of children's dietary diversity between agriculture and fishpond family group when the dietary diversity was omitting 10 grams minimum intake (p-value=0.184), while, using 10 grams minimums intake (p=0.024), there is a difference. Conclusions: Using 10 grams minimum had shown to strengthened the relationship between dietary diversity and adequacy. Further research is needed to find other minimum requirement in different kind of population to find differences among them.